The writing desk [large type] - Hauck, Rachel, 1960- (Thorndike Press, a part of Gale, a Cengage Company, 2017)
It's 1902, and socialite Birdie Shehorn has spent four years at Wellesley instead of doing what's expected of her: finding an appropriately rich husband. So now her parents have arranged for her to marry. But Birdie wants to write, something women of the time aren't encouraged to do. In the present, Tenley Roth has penned a best-seller and become a star. She's expected to write a second, but she can't because she's been in a state of shock ever since her father's death. The mother who left her when Tenley was nine has asked her to move in with her and care for her through 12 weeks of chemo treatments. To top everything off, Tenley's boyfriend has surprised her with an insistent marriage proposal. Two strong women from two different eras, both writers facing unpleasant futures, share many similarities as they strive to achieve their goals regardless of any obstacles. And it all starts with a very special writing desk.